Je voudrais que l'on me montre comment faire le résultat svp (3*10 puissance 8) * (5*10 puissance 7) = (6*10 puissance 15) / ( 2 puissance 7 ) = (3*10 puissance 8 ) * ( 7*10 puissance -5) = 3.9*(10 puissance -2 ) puissance 2 / 3*10 puissance -6 =

1

Réponses

2012-10-07T11:01:03+02:00

(3*10 puissance 8) * (5*10 puissance 7) = (6*10 puissance 15) / ( 2 puissance 7 ) = (3*10 puissance 8 ) * ( 7*10 puissance -5) = 3.9*(10 puissance -2 ) puissance 2 / 3*10 puissance -6 =

 

(300000000)*(50000000)=(6*10 puissance 15) / (128) = (300000000)*( 7*10 puissance -5) = 3.9 * (0.1) puissance 2 / 3*10 puissance -6 =

 

1.5*10 puissance 16 = 4.6875*10 puissance 13 = 21000 = 0.039 / 3*10 puissance -6  =

 

 

1.5*10 puissance 16 = 4.6875*10 puissance 13 = 21000 = 13000